Crowding (at) the margins: Investigating the unequal distribution of housing space in Germany - Sebastian Kohl; Max Friedrich Steinhardt; Luca Stella; Simon Voss (Freie Universität Berlin, School of Business & Economics, 2024)
This study explores the factors influencing household overcrowding using longitudinal survey data from Germany spanning the years 1985 to 2022. As average square meters per capita have declined for urban tenants, we find that overcrowding rates have substantially increased since 2012: By 2022, 11% of the population lived in overcrowded housing (Eurostat definition), while up to 19% of individuals subjectively felt overcrowded. At the same time, under-occupation also rose, with 39% of dwellings objectively classified as under-occupied, and 16% of residents subjectively perceiving their homes as under-occupied. We demonstrate that the likelihood of entering, experiencing, and remaining in overcrowded housing increases in early adulthood and decreases over the life cycle. Moreover, we find that, after controlling for socio-demographic characteristics such as the number of children or a migration background, economic factors contribute relatively little to explaining the likelihood of living in an overcrowded household. In policy terms, our paper highlights a misallocation of housing space and the need for housing policies to target particular vulnerable groups at high risk of overcrowding.
urn:nbn:de:kobv:188-refubium-45709-3
Keywords: D31; I32; J13; R21; R31; 330; Housing affordability; Living space; Inequality; Germany; Overcrowding; Well-being